Relationship between teat-end condition, udder cleanliness and bovine subclinical mastitis - Manzi, Marcela de Pinho [UNESP]; Nobrega, Diego Borin [UNESP]; Faccioli, Patricia Yoshida [UNESP]; Troncarelli, Marcella Zampolli [UNESP]; Menozzi, Benedito Donizete [UNESP]; Langoni, Hélio [UNESP] (Elsevier B.V., 2012)
The aims of the present study were to relate intramammary infection (IMI) occurrence and somatic cell count (SCC) with teat-end condition (TEC) and udder cleanliness (UC). Milk samples from 1931 teats were evaluated according to the presence of IMI and SCC. Scores were applied to teats according to the TEC and to UC. Teats ends with a very rough ring had the largest number of IMI when compared to the other three categories, as well as animals with dirtier udders. The change in a TEC score increased by around 30% the chance of IMI. Also, the chance of the animal developing IMI increased by approximately 47% when the UC score increased. No significant association between both scores and quarter SCC was found. It can be concluded that animals with very rough teat end rings and very dirty udders have a greater predisposition to IMI. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Bovine mastitis; Teat-end condition; Udder cleanliness